1998
DOI: 10.1103/physrevlett.80.2141
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency Dynamics in a Molten Binary Alloy

Abstract: Heavily damped excitations are found in molten Li 4 Pb by inelastic neutron scattering. The experiment covered a kinematic range which enabled an unambiguous characterization of such excitations by means of the study of the wave vector dependence of their frequencies, lifetimes, and signal amplitudes. It is shown that the excitations being sampled exhibit features which substantially deviate from those expected for the propagation of an acoustic mode (which should involve in-phase atomic displacements). [S0031… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
36
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 19 publications
7
36
2
Order By: Relevance
“…The departure from full classical behavior is also attested by the large value found for the mean-square displacement, since a large portion of it is attributable to zero-point motions. The finding of strong anomalous dispersion contrasts with phenomena observed in more complex fluids such as molten alloys or water, 26 where the dispersion is known to arise from an admixture of modes of different character. The presence of such relatively long-lived excitations thus provides a microscopic explanation for the anomalous behavior observed in its heat and momentum-transport properties.…”
Section: Discussioncontrasting
confidence: 43%
“…The departure from full classical behavior is also attested by the large value found for the mean-square displacement, since a large portion of it is attributable to zero-point motions. The finding of strong anomalous dispersion contrasts with phenomena observed in more complex fluids such as molten alloys or water, 26 where the dispersion is known to arise from an admixture of modes of different character. The presence of such relatively long-lived excitations thus provides a microscopic explanation for the anomalous behavior observed in its heat and momentum-transport properties.…”
Section: Discussioncontrasting
confidence: 43%
“…Recently, MD simulation has been extensively applied to the study of both the structure and the dynamic properties of liquid metals whereas liquid alloys have received less attention, especially in the case of dynamic collective properties. Since the pioneer MD simulation of Na-K liquid alloy 1 the majority of studies have been centered on the alloy Li 4 Pb. In a MD simulation of this system Bosse et al 2 observed the existence of high-frequency peaks in the partial Li-Li dynamic structure factors at rather large wave vectors.…”
Section: Introductionmentioning
confidence: 99%
“…Several theoretical and CMD results for He-Ar and He-Ne mixtures have suggested that either the fast and slow sound merge into the hydrodynamic sound [8,14], or that the fast sound disappears at q h and the slow sound merges into the hydrodynamic one with a predicted value [19,20] of q h ≈ 0.07Å −1 . A similar value for q h has recently been obtained for liquid Li 4 Pb by both INS and by CMD calculations [11,15]. Recent CMD calculations [16], which followed the INS measurements of Bafile et al [12], for the He 0.77 Ne 0.23 gas mixture at two densities, showed a clear crossover from hydrodynamics to fast and slow modes at 0.2 q/Å −1 0.5; moreover, it was obtained that q h ≈ 0.2, which is substantially greater than previous estimates.…”
Section: Introductionmentioning
confidence: 49%
“…It was followed by the CMD results for liquid Li 4 Pb [7], where a new, high-frequency mode, allegedly supported by the light Li atoms only, (the so-called "fast sound") was found. This finding spurred a wealth of experimental [8][9][10][11][12][13], computer simulation [8,[14][15][16][17] and theoretical [18][19][20][21][22] works focused on the investigation of the nature and properties of the collective excitations in liquid binary systems.…”
Section: Introductionmentioning
confidence: 99%